Perspectives on Recent Advances in the Speed of High Performance Liquid Chromatography - Carr, Peter W. (2011)
Perhaps the most consistent trend in the development of HPLC since its inception in the 1960’s has been the continuing reach for ever faster analyses. The pioneering work of Knox, Horvath, Halasz, and Guiochon set forth a theoretical framework that was used early on to improve the speed of HPLC, primarily through the commercialization of smaller and smaller particles. Over the past decade, approaches to improving the speed of HPLC have become more diverse, and now practitioners of HPLC are faced with the difficult task of deciding which of these approaches will lead them to the fastest analysis for their application. Digesting the rich literature on the optimization of HPLC is a difficult task in itself, which is further complicated by contradictory marketing messages from competing commercial outlets for HPLC technology. In this perspectives article we provide an overview of the theoretical and practical aspects of the principal modern approaches to improving the speed of HPLC. We present a straightforward theoretical basis, informed by decades of literature on the problem of optimization, that is useful for comparing different technologies for improving the speed of HPLC. Through mindful optimization of conditions high performance separations on the sub-minute timescale are now possible and becoming increasingly common under both isocratic and gradient elution conditions, and the continued development of ultrafast separations will play an important role in the development of two-dimensional HPLC separations. Despite the relatively long history of HPLC as an analytical technique, there is no sign of a slow-down in the development of novel HPLC technologies.